Puissance et connaissance animales chez les Kaingang du Brésil méridional - da Rosa, Rogério Reus Gonçalves; Crépeau, Robert R. (Anthropologica, 2020)
Among the Kaingang of southern Brazil, animals appear in several stories that describe the origin of technical and ritual knowledge. For instance, one such story recounts how, after the flood, animals were the first organisers and officiants of the Kikikoi, a great funeral ritual considered to be the most important expression of Kaingang culture and identity. The Kaingang claim that they learned the ritual’s songs and dances from the animals. In this article, we analyse the relationship between animal skills and the practice of Kaingang shamans. We propose a reflection on humans’ relation to the animal world construed as part of a hierarchy of powers and, more specifically, of shared animal and human skills and powers of action. The concept of master entity emerges as a key for interpreting the practice, authority, and skills of shamans and other leaders.